Improving the Usability and User Experience of a Ticketing and Knowledge Base Web Application: A Case Study of the ESDM 136 Contact Center - Ridwan Afandi; Santoso, Harry Budi (The Indonesian Journal of Computer Science, 2025)
The Ministry of Energy and Mineral Resources (MEMR) established the ESDM 136 Contact Center to improve public service accessibility and quality, supported by ticketing and a knowledge-based web application for managing complaints. However, in 2023, the average response time for requests exceeded the SLA, indicating a need to evaluate the application systems to improve service efficiency. This study addresses the poor usability and user experience of the ticketing and knowledge-based web applications, as evidenced by below-average scores on the UEQ and PSSUQ. Utilizing a mixed-methods approach, including usability testing, cognitive walkthroughs, and open-ended questionnaires, this research identified twenty-one usability issues. Eighteen design improvements, guided by user-centered design principles, were implemented in a high-fidelity prototype. Post-improvement PSSUQ evaluations showed significant improvements, with post-intervention scores falling within the "above standard" range for all measured categories and an overall score improvement from 3.17 to 2.51.